ANALISIS PENGARUH TINGKAT KEBISINGAN PADA STASIUN STERILIZER TERHADAP KUALITAS TIDUR OPERATOR - Faradila Ananda Yul; Dedi Dermawan; Fira Putri Aldiyanti (Fakultas Teknik UMRI, 2020)
Palm Oil Mill PT. Surya Intisari Raya, Sei Lukut is a plantation company engaged in the commodity palm oil FFB (Fresh Fruit Bunches), with output in the form of CPO (Crude Palm Oil) and Palm Kernel (PK). There are 13 processing stations at PKS that have high noise levels, one of which is a sterilizer station which can disrupt operator psychology, namely Sleep Disturbance. In the field survey, it was found that operators experienced concentration problems such as drowsiness, and not all of them used ear protection in the form of earplugs/earmuffs. Therefore, it is necessary to identify the noise level at the sterilizer station and to analyze its effect on the operator's sleep quality using an observational analytic cross-sectional approach. Noise in the workplace was measured using a sound level meter and the sleep quality of workers was measured using the Pittsburgh Sleep Quality Index (PSQI) questionnaire. Based on the results of noise level measurements, 4 processes have noise above the Threshold Limit Value, namely Deaeration of 89.824 dB, Containment of 92.548 dB, Peak BlowDown by 2 of 96.45 dB, and Final of 102.77 dB. Based on the results of the Pittsburgh Sleep Quality Index (PSQI) questionnaire, 100% of Morning Shift and Night Shift workers have poor sleep quality. To overcome this problem, several suggestions were made, namely to carry out periodic health checks for operators, ensure that operators who are exposed to noise always wear an earplug/earmuff, and minimize exposure to noise above the NAB to operators by keeping noise points away from the operator's premises.